2011
DOI: 10.1111/j.1365-2249.2010.04314.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and periodontal disease: discrimination of antibody responses to pathogenic and commensal oral bacteria

Abstract: SummarySmoking is an independent risk factor for the initiation, extent and severity of periodontal disease. This study examined the ability of the host immune system to discriminate commensal oral bacteria from pathogens at mucosal surfaces, i.e. oral cavity. Serum immunoglobulin (Ig)G antibody reactive with three pathogenic and five commensal oral bacteria in 301 current smokers (age range 21-66 years) were examined by enzyme-linked immunosorbent assay. Clinical features of periodontal health were used as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 51 publications
7
32
0
2
Order By: Relevance
“…Thus, while clearly facilitating impressive molecular microbiology advances, research strains of P. gingivalis may not always be the most relevant to in vivo situations. There were no statistically significant differences in the intensity of the humoral response to P. gingivalis between current smokers and non-smoking subjects with AP, in keeping with the findings of Hayman et al , who have recently reported that correlations between pathogen and commensal antibody ratios in individuals with periodontitis disappear in those with aggressive disease 7 . This may be partly explained by our finding that current smokers with AP are more likely to be currently infected with P. gingivalis than non-smokers with AP.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, while clearly facilitating impressive molecular microbiology advances, research strains of P. gingivalis may not always be the most relevant to in vivo situations. There were no statistically significant differences in the intensity of the humoral response to P. gingivalis between current smokers and non-smoking subjects with AP, in keeping with the findings of Hayman et al , who have recently reported that correlations between pathogen and commensal antibody ratios in individuals with periodontitis disappear in those with aggressive disease 7 . This may be partly explained by our finding that current smokers with AP are more likely to be currently infected with P. gingivalis than non-smokers with AP.…”
Section: Discussionsupporting
confidence: 90%
“…The great majority 5-6, 22, 25-26 , but not all 7 , have shown that smoking reduces the antibody response to P. gingivalis , particularly IgG. We show that the total IgG response mounted against low passage clinical isolates (5607, 10208C and 1052), but not laboratory strains, of P. gingivalis (33277 and W83) is significantly suppressed in smokers with CP.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…An association between oral bacteria and systemic antibody response is well-established in individuals who have different degrees of periodontal disease; serum antibody levels to oral pathogens, such as P. gingivalis, correlate with severity of periodontal disease 32 . However, in the general population, the association between serum antibody levels to oral pathogenic bacteria and periodontal disease status is inconsistent; other factors, such as smoking status, can influence the immune response (i.e., IgG levels) 19, 20 .…”
Section: Discussionmentioning
confidence: 99%